2020
DOI: 10.1167/tvst.9.7.16
|View full text |Cite
|
Sign up to set email alerts
|

Localized Photoreceptor Ablation Using Femtosecond Pulses Focused With Adaptive Optics

Abstract: Purpose The development of new approaches to human vision restoration could be greatly accelerated with the use of nonhuman primate models; however, there is a paucity of primate models of outer retina degeneration with good spatial localization. To limit ablation to the photoreceptors, we developed a new approach that uses a near-infrared ultrafast laser, focused using adaptive optics, to concentrate light in a small focal volume within the retina. Methods In the eyes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
(84 reference statements)
0
15
0
Order By: Relevance
“…Following a preliminary attempt (see Note S3 ), we decided not to pursue this approach further for transplantation studies, although it was possible that we could have reduced these problems with a lower light exposure. Instead, we adopted a laser lesion method recently developed in our laboratory and described in detail in Dhakal et al (2020) . Selective photoreceptor ablation was observed after exposing host photoreceptors to ultrafast pulses of light delivered using the adaptive optics system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a preliminary attempt (see Note S3 ), we decided not to pursue this approach further for transplantation studies, although it was possible that we could have reduced these problems with a lower light exposure. Instead, we adopted a laser lesion method recently developed in our laboratory and described in detail in Dhakal et al (2020) . Selective photoreceptor ablation was observed after exposing host photoreceptors to ultrafast pulses of light delivered using the adaptive optics system.…”
Section: Resultsmentioning
confidence: 99%
“…While inherited models of retinal degeneration have recently been identified in nonhuman primates ( Moshiri et al., 2019 ; Peterson et al., 2019 ), at present there is no readily available genetic primate model of retinal degeneration. In this study, we used a recently developed model of selective photoreceptor ablation by using femtosecond pulses of near infrared (NIR) light onto the retina with adaptive optics ( Dhakal et al, 2020 ). This method of photoreceptor ablation leads to minimal disruption of the surrounding tissue, including the retinal pigment epithelium (RPE).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that even in areas of the primate retina where photoreceptor ablation was performed under overlying RGCs, their function was not impaired. 17 In contrast to much of the remodeling literature, in the present study the therapeutic ChrimsonR was present before photoreceptor ablation and was periodically stimulated for the purposes of this study. Although experimental optogenetic activation was for no more than 15 min during relatively infrequent imaging sessions, this could have been sufficient to preclude remodeling that might be driven in part by loss of visually driven activity in inner retina.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we use an acute photoreceptor ablation approach 17 to create a micro-scotoma in the adult primate, depriving a subset of foveal RGCs of their photoreceptor input. We use fluorescence fundus imaging and structural and functional AOSLO to follow optogenetic expression and responsivity of RGCs with and without photoreceptor input for 12 weeks after photoreceptor ablation and in a second animal demonstrate that optogenetic-mediated RGC activity persists for at least 12 months after the loss of photoreceptor input.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies suggested that longer wavelength lasers result in damage of the outer retina layers, while shorter wavelength lasers damage all retinal layers [ 8 ]. Other studies have combined femtosecond laser with adaptive optics to achieve focal photoreceptor ablation in NHPs [ 9 ]. The ability to selectively limit damage to the outer retina layer can be useful as RPE disruption compromises the blood–retina barrier and evokes a strong immune response, whereas damage to the inner retina impedes functional re-circuiting.…”
Section: Ird Nhp Models Created Using Chemical and Laser Methodsmentioning
confidence: 99%